Scenario tendencies of professional genesis of investigators of pre-trial investigation agencies of the National police of Ukraine - N. E. Miloradova (Law and Safety)
The author of the article has presented results of a thorough analysis of international (A. Adler, E. Bern, R. Brasington, T. Keller, C. Toich, S.B. Karpman, K. Steiner, etc.) and domestic (K. O. Abulkhanova-Slavska, O. O. Bodalov, Ye. I. Holovakha, E. F. Zeier, Ye. O. Klimov, N. S. Priazhnikova, Ye. Yu. Priazhnikov, S. L. Rubinshtein, E. E. Symaniuk, etc.) approaches to consider specific features of professional development of individuals and formation of scenario tendencies for self-deployment within personal and professional fields.